PENGEMBANGAN MATERI AJAR ILMU PENGETAHUAN SOSIAL - Henni Endayani (IJTIMAIYAH Jurnal Ilmu Sosial dan Budaya, 2017)
The material IPS uses social sciences materials selected and adapted to the purpose of teaching and education. Educators who teach the material IPS should know the shapes of teaching materials IPS. This is very useful, so that this understanding can be used to develop teaching materials IPS. Ability to develop teaching materials that IPS will enable us to improve the learning activities in a higher quality IPS, whose purpose is none other than that to make the students understand the social environment, human beings with all their activities and interactions between them.